2014
DOI: 10.1007/s00367-014-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual-frequency ADCPs measuring turbidity

Abstract: A pair of self-contained acoustic Doppler current profilers (SC-ADCPs) operating with different frequencies were moored on a muddy sea bottom at about 20 m depth in the Bay of Vilaine off the French Atlantic coast. With their acoustic beams oriented upwards, the SC-ADCPs ensonified most of the water column. The results of several months of in situ recorded echo intensity data spanning 2 years (2003 to 2004) from the dual-frequency ADCPs are presented in this paper. The aim was to estimate suspended particle m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…(3), the Coriolis frequency acts in favor of trapping by the surface for a near-equatorial plume. This feature is observed in the BIOZAIRE cruises (see salinity section of (Jourdin et al 2006), where the Congo plume is surface trapped with no evidence of coastal current (it would have been necessarily noticeable if the plume was bottom influenced). The shape of the surface bulge is also observed to spread like a lens in the satellite observations of CDM absorption length of GlobColour data (Maritorena et al 2010) and sea surface salinity of SMOS data (Boutin et al 2012) (see Fig.…”
Section: Near-field Plume Morphologymentioning
confidence: 84%
See 1 more Smart Citation
“…(3), the Coriolis frequency acts in favor of trapping by the surface for a near-equatorial plume. This feature is observed in the BIOZAIRE cruises (see salinity section of (Jourdin et al 2006), where the Congo plume is surface trapped with no evidence of coastal current (it would have been necessarily noticeable if the plume was bottom influenced). The shape of the surface bulge is also observed to spread like a lens in the satellite observations of CDM absorption length of GlobColour data (Maritorena et al 2010) and sea surface salinity of SMOS data (Boutin et al 2012) (see Fig.…”
Section: Near-field Plume Morphologymentioning
confidence: 84%
“…In fact, in its first approximation, the temperature would not influence density much, as the thermocline is not very marked and lies under a sharp halocline due to the freshwater discharge (Jourdin et al 2006;Vangriesheim et al 2009). The propagation speed of the gravity internal waves in a two-layer model is formally c i 5…”
mentioning
confidence: 97%
“…In Figure 4, it can be seen that the water condition near the bottom was categorized as turbid with visibility ranging from 5 to 10 m. Based on several factors that have been described, the transmission losses correction factors (absorption and distance) became important because they were related to sound signal propagation. The factors affecting sound propagation recorded by ADCP were distance, medium, and coefficient of attenuation [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that turbidity measurements obtained by optical (e.g., XR620 and the OBS-3A turbidity and temperature monitoring systems) and acoustic techniques can be combined with in situ water samples to determine SSC variability in the bottom boundary layer and throughout the water column (Yang et al 2007;Yuan et al 2008;Jourdin et al 2014;Shi et al 2014). In the present study, the XR620 was immersed in tanks filled with water samples collected in the field.…”
Section: Ssc Calculationmentioning
confidence: 99%